Cardiovascular Fitness Assessment through 3 Minutes Step Test in Adults of Lahore during COVID-19 Pandemic - Raza, Ali; Sajjad, Sajjad Ali; Rana, Arif Ali; Ijaz, Arshia; Asif, Muhammad; Zulfiqar, Abdullah (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2021)
At the end of the year, 2019 world witnessed a disease, which is still affecting the world, this disease was named Corona Virus Disease -19 (COVID-19). It is a highly infectious disease that causes severe acute respiratory syndrome. Objective: To find out the impact of COVID-19 on the cardiac fitness of young and middle-aged adults. Methods: A cross-sectional study was conducted at ON-Campus Physiotherapy Clinic at University of Management and Technology, Lahore. Convenient sampling was used. The sample size was 437. Healthy participants from both genders aging 17-45 years were recruited in the study. A self-designed questionnaire validated through a pilot study was used to record the data. Three minutes step test was performed and pre and post-test Cardiac rate were recorded. IBM SPSS Statistics for Windows was used to record and analyze all data. Results: Results showed that the female participants were 271 (59.7%) while males were 176(41.3%), young adults proportion was 76% while middle-aged adults was 24%.The overall results of the post-test 3-minutes step test show that a majority of the population30.7 % (n=134) had excellent cardiac rate, a good proportion of the sample had the same value for Good and above-average cardiac rates (f=22.4 %, n= 98) while fewer number participants fall in rest of the categories such as average, below average, poor and very poor ( 12. %, 7.1%, 3.0 %, 2.3 %) respectively. Conclusions: The study concluded that the overall cardiac capacity of young and older adults is not affected by the pandemic but the females have a better cardiac condition as compared to men.